Declining NPF Threatens Islamic Finance Stability: Unveiling Negative Correlation with CAR (2021-2023) through Robust Statistical Analysis - Isman, I; Widodo, Prima Ariyo; Risdayani, R (Universitas Muhammadiyah Surakarta, 2023)
The aim of this research is to investigate the dynamics of Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR) in Islamic finance from 2021 to 2023. Robust statistical methods, including Pearson and Spearman correlation tests, were used to examine the relationship between NPF and CAR. The findings indicate a significant negative correlation between NPF and CAR, with a significance value below 0.05. The strength of this inverse relationship is underscored by Pearson and Spearman correlation coefficients of -0.342 and -0.486, respectively, signifying a robust association. This negative correlation implies that as NPF increases, the CAR tends to decrease, and vice versa. The research provides valuable insights into the field of Islamic finance by highlighting the potential threat posed by declining non-performing financing (NPF) to the stability of financial institutions. Understanding these dynamics is important for stakeholders to develop strategic measures that maintain the Capital Adequacy Ratio and ensure the resilience of Islamic financial systems between 2021 and 2023.